Study protocol and preliminary baseline characteristics of a VA multi-site, mixed methods, randomized controlled study evaluating supported employment provided to veterans with opioid use disorder - Mercy Mumba; Teresa Granger; George Mugoya; Stephen Brackett; Junfei Lu; Emily Lund; Charles Lynn; Anchal Ghera; Whitney Gay; Lori Davis (Annals of General Psychiatry)
Abstract Opioid Use Disorder (OUD) is a pervasive and devastating public health crisis that continues to take a heavy toll on individuals and communities across the United States. In 2021, approximately 473,000 veterans misused opioids in the past year. In the context of their military service and post-service life, Veterans with OUD often encounter unique barriers to recovery, including the reintegration into civilian society and the pursuit of stable, meaningful employment. The path to recovery from OUD is inextricably linked to the restoration of a stable and purposeful life, a fact underscored by the interplay of substance use, mental health, and employment outcomes. These factors necessitate a comprehensive approach to treatment that extends beyond mere pharmacological interventions. One such approach is Individual Placement and Support (IPS), a well-established evidence-based practice that focuses on supporting individuals with severe mental illness in their pursuit of competitive employment. The primary objective of this manuscript is to describe a two-arm, multi-site RCT designed to rigorously evaluate the efficacy of IPS when provided to veterans with OUD and provide the baseline demographics and characteristics of the participants who have enrolled to date. The central hypothesis guiding this research is that IPS can significantly improve vocational, psychosocial, and treatment outcomes of veterans in recovery from OUD, ultimately leading to a more successful reintegration into civilian life. Our study is timely as the VA has expanded IPS services to veterans with SUD this past year. Thus, this study is one of the first to examine IPS in a subpopulation of veterans with a SUD and may provide actionable data to support sustainment of IPS with this population.